Photoluminescence and electrophysical properties of p-type ZnO layers implanted with V Group elements - Kotlyarevsky, M.B.; Rogozin, I.V.; Marakhovsky, O.V. (Functional Materials, 2005)
Ion implantation of arsenic and nitrogen into zinc oxide film (As and N being acceptor impurities in ZnO) has been shown to result in formation of the hole conductivity only if the film is annealed in the presence of oxygen radicals. The ion implantation and sub- sequent anneal influence not only the electric properties but also the photoluminescence spectra of ZnO:Ga:As⁺ (ZnO:Ga:N⁺) layers. The luminescence bands due to As and N introduction appear in the UV and visible spectral regions. Показано, що iонна iмплантацiя миш'яку (азоту) у плiвку оксиду Цинку (As i N як акцепторна домiшка у ZnO) може приводити до формування дiркового типу провiдностi тiльки у випадку вiдпалу в атмосферi радикалiв кисню. Iонна iмплантацiя i наступний вiдпал впливають не тiльки на електричнi властивостi шарiв :Ga:As⁺ ZnO (ZnO:Ga:N⁺), але й на iхнi спектри фотолюмiнесценцii. Смуги люмiнесценцii, що викликанi впровадженням As i N, спостерiгаються в ультрафiолетовiй i видимiй областях спектра. Показано, что ионная имплантация мышьяка (азота) в пленку оксида Цинка (As и N как акцепторная примесь в ZnO) может приводить к формированию дырочного типа проводимости только в случае отжига в атмосфере радикалов кислорода. Ионная имплантация и последующий отжиг влияют не только на электрические свойства слоев ZnO:Ga:As⁺ (ZnO:Ga:N⁺), но и на их спектры фотолюминесценции. Полосы люминесценции, которые вызваны внедрением As и N, наблюдаются в ультрафиолетовой и видимой областях спектра.